USE OF PRACTICAL-ORIENTED APPROACH IN VOCATIONAL TRAINING FUTURE TEACHERS - I.O. Palshkova (Academy of Cognitive and Natural Sciences, 2004)
The article shows the using of practical-oriented approach in professional training of future teachers.